In the Room Where It Happens: Autonomy and Discretion in Home Visitors' Information and Referral Actions - Marina, Sarah. (2017)
Abstract: This thesis explores how home visitors in the Healthy Families Massachusetts (HFM) program—those who operate at the interface between program and client in the manner of a "street level bureaucrat" (Lipisky, 1980)—analyze and implement program policy via their information and referral service actions on a day-to-day basis. The information and referral actions of HFM home visitors at five sites were explored to determine if profiles of the use of these actions would be found, and if so, how they related to programmatic, client, and home visitor characteristics. Four profiles were found in home visitors application of support services, with an impact noted based on home visitor location. Support services are activities which fall in a grey area outside of written HFM program guidelines, and variation in how they are applied is an indication of home visitor discretion and autonomy.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Francine Jacobs.; Committee: Jessica Goldberg, and Laurie Goldman.; Keyword: Urban planning.